Peripheral Nerve Regeneration in Interleukin 6–Deficient Mice - Inserra, Michelle M; Yao, Mike; Murray, Richard; Terris, David J (Archives of otolaryngology--head & neck surgery, 2000)
BACKGROUND Interleukin 6 (IL-6) is a multifunctional cytokine with effects on central and peripheral neurons. OBJECTIVE To investigate the role of IL-6 in peripheral nerve regeneration by comparing IL-6 knockout and wild-type mice in a sciatic nerve model of injury and repair. DESIGN/SUBJECTS Forty C57/BL6 (wild-type) and 40 IL-6 knockout mice were randomly assigned to 1 of 4 groups: sham surgery, sciatic nerve crush injury, sciatic nerve transection without repair, and sciatic nerve transection with epineurial suture repair. Walking tracks were assessed preoperatively and postoperatively at 10-day intervals for 50 days by means of a previously described mouse sciatic functional index. Distal segments of the sciatic nerves were harvested at the completion of the study for histomorphometric evaluation. RESULTS The wild-type and knockout mice that underwent sham surgery showed similarly unimpaired function (P =.64 on day 50). The IL-6 knockout mice with the crush injury demonstrated decreased function on day 10 compared with the wild-type mice (P<.01) but completely recovered by day 40 (P =.55). Both IL-6 knockout and wild-type mice that underwent nerve transection without repair failed to recover function (P =.06 on day 50). There was no statistical difference in recovery between wild-type and IL-6 knockout mice that underwent nerve transection with epineurial suture repair (P =.30 on day 50). The morphometric data showed no significant differences in distal axon count between the wild-type and knockout mice after suture repair or crush injury (P>.32). CONCLUSIONS The absence of IL-6 does not appear to impair peripheral nerve recovery after sciatic nerve injury. Although in vitro and in vivo studies suggest a role for IL-6 in peripheral nerve physiology, this cytokine does not appear to have a substantial effect on functional recovery in a mouse sciatic nerve injury and repair model.Arch Otolaryngol Head Neck Surg. 2000;126:1112-1116-->